Preclinical efficacy and safety evaluation of BD211 autologous CD34+ hematopoietic stem cell injection for transfusion-dependent β-thalassemia in NCG-X mice - Xuedong Dai; Xuedong Dai; Zike Li; Shuang Chen; Ying Huang; Sikai Ling; Quanjun Wang; Qi Wang (Frontiers in Cell and Developmental Biology)
IntroductionAutologous CD34+ hematopoietic stem cell-based therapies have shown promise in addressing therapeutic needs. However, a comprehensive evaluation of their efficacy and safety is crucial before clinical application. This study aimed to assess the efficacy and safety profile of BD211 autologous CD34+ hematopoietic stem cell injection in NCG-X mice.MethodsNCG-X mice were administered BD211 intravenously at doses of 4.0 × 105 and 1.2 × 106 cells per mouse, followed by withdrawal and observation for 13 weeks. Efficacy was evaluated by monitoring the engraftment and differentiation of BD211 into human erythroid cells within the mouse bone marrow and blood. Safety was assessed through clinical observation, pathology, organ weight measurements, and histopathology. Toxicokinetic studies and distribution of BD211 were determined via validated quantitative PCR.ResultsMortality was observed in all groups of mice with no correlation to dose or BD211. No abnormal effects related to BD211 administration on clinical responses, body weight, or food intake were observed. BD211 successfully engrafted and differentiated into human erythroid cells within the mouse bone marrow and blood.ConclusionThe no observed adverse effect level of BD211 was established at 1.2 × 106 cells per mouse. BD211 shows potential as a safe therapeutic approach for treating transfusion-dependent thalassemia.